4-(3-Alkyl/benzyl-guanidino)benzenesulfonamides as selective carbonic anhydrase VII inhibitors - Morteza Abdoli; Simone Giovannuzzi; Claudiu T. Supuran; Raivis Žalubovskis (Taylor & Francis Group, 2022)
The treatment of chronic neuropathic pain remains one of the most challenging of all neurological diseases and very much an art. There exists no consensus for the optimal management of this condition at the moment. Gaining inspiration from recent studies which pointed out the involvement of brain-associated carbonic anhydrase (CA, EC 4.2.1.1) isoform VII in the pathology of various neurodegenerative diseases, which highlighted the relationship between selective inhibition of this isozyme and relieve of neuropathic pain, herein we report the synthesis and CA VII inhibitory activity of novel 4-(3-alkyl/benzyl-guanidino)benzenesulfonamides. Ten benzyl-substituted and five alkyl-substituted 4-guanidinobenzenesulfonamide derivatives were obtained, some of which (7c, 7h, 7m and 7o) exhibited satisfactory selectivity towards CA VII over CA I and II, with KI-s in the subnanomolar range and good selectivity indexes for inhibiting the target versus the off-target isoforms.